1987
DOI: 10.1021/bi00381a013
|View full text |Cite
|
Sign up to set email alerts
|

Covalent labeling of a high-affinity, guanyl nucleotide sensitive parathyroid hormone receptor in canine renal cortex

Abstract: Putative parathyroid hormone (PTH) receptors in canine renal membranes were affinity labeled with 125I-bPTH(1-34) using the heterobifunctional cross-linking reagent N-hydroxysuccinimidyl 4-azidobenzoate. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed the presence of a major 85,000 molecular weight (Mr) PTH binding component, the labeling of which was inhibited by nanomolar concentrations of unlabeled PTH and by micromolar concentrations of 5'-guanylyl imidodiphosphate [Gpp-(NH)p]. Labeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The detection of two species of PTH receptor in this as well as other studies (Demay et al, 1985;McKee & Murray, 1985) agrees with the physiological observation that there may be at least two different types of PTH receptors coupled to different second messengers. Photoaffinity labelling of PTH receptors on dog kidney membrane has been performed with several photoaffinity labels (Coltrera et al, 1981;Draper et al, 1982;Goldring et al, 1984;Nissenson et al, 1987). Our results obtained with the heterobifunctional, photoreactive reagent HSAb were in general agreement with previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The detection of two species of PTH receptor in this as well as other studies (Demay et al, 1985;McKee & Murray, 1985) agrees with the physiological observation that there may be at least two different types of PTH receptors coupled to different second messengers. Photoaffinity labelling of PTH receptors on dog kidney membrane has been performed with several photoaffinity labels (Coltrera et al, 1981;Draper et al, 1982;Goldring et al, 1984;Nissenson et al, 1987). Our results obtained with the heterobifunctional, photoreactive reagent HSAb were in general agreement with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…Using a classical radioligand binding assay, parathyroid hormone (PTH) receptors have been identified on chicken (Nissenson & Arnaud, 1979;McKee & Murray, 1985), rat (Chansel et al, 1977), dog (Segre et al, 1979;Teitelbaum et al, 1982), bovine (Zull et al, 1977) and rabbit (Kremer et al, 1982) bone and kidney tissues. However, structural identification using photoaffinity labelling techniques has been performed mainly on dog kidney membrane (Coltrera et al, 1981;Draper et al, 1982;Goldring et al, 1984;Nissenson et al, 1987). Despite the above information on animal models, the functional and structural characteristics of human PTH receptors have not yet been defined.…”
Section: Introductionmentioning
confidence: 99%
“…Parathyroid hormone (PTH) 1 is the primary regulator of calcium and phosphate homeostasis in higher animals (1). This 84-amino acid peptide and truncated forms such as the 1-34 or 1-36 fragments initiate the biological actions of PTH through a specific receptor (PTHR) on the plasma membrane in target tissues, primarily kidney and bone (2)(3)(4)(5). Recently, the cDNAs of PTHR from rat, mouse, and human cells have been cloned (6 -10), and both transient and stable transfection of PTHR has been described (7,11,12).…”
mentioning
confidence: 99%
“…All probes tested label a major protein with a n apparent molecular weight of 75-85 kDa (Pun et al, 1988;Goldring et al, 1984;Nissenson et al, 1987;Wright et al, 1987;Nissenson et al, 1988;Karpf et al, 1991). In some studies, minor labeling of another protein has been observed (Pun et al, 1988;Nissenson et al, 1987;Wright et al, 1987;Nissenson et al, 1988;Karpf et al, 19911, which probably represents proteolytic products of the 75-85 kDa protein (Nissenson, et al, 1987). The similar dose response curves for PTHmediated cAMP and [Ca" 'I, increase, together with binding and photoaffinity studies, led us to suggest that the same PTH receptor is coupled to two signal transduction systems (Yamaguchi et al, 1987a).…”
Section: Discussionmentioning
confidence: 99%